Machine learning identifies ICU outcome predictors in a multicenter COVID-19 cohort - Magunia, Harry; Lederer, Simone; Verbuecheln, Raphael; Gilot, Bryant; Koeppen, Michael; Häberle, Helene; Mirakaj, Valbona; Hofmann, Pascal; Marx, Gernot; Bickenbach, Johannes; Nohe, Boris Alexander; Lay, Michael; et al. (Critical care, 2021)
Intensive Care Resources are heavily utilized during the COVID-19 pandemic. However, risk stratification and prediction of SARS-CoV-2 patient clinical outcomes upon ICU admission remain inadequate. This study aimed to develop a machine learning model, based on retrospective & prospective clinical data, to stratify patient risk and predict ICU survival and outcomes.